Case Report: Left Ventricular Unloading Using a Mechanical CPR Device in a Prolonged Accidental Hypothermic Cardiac Arrest Treated by VA-ECMO – a Novel Approach - Amacher, Simon A.; Quitt, Jonas; Hammel, Eva; Zenklusen, Urs; Darwisch, Ayham; Siegemund, Martin (Frontiers in Cardiovascular Medicine, 2021)
We recently treated a 36-year-old previously healthy male with a prolonged hypothermic (lowest temperature 22.3°C) cardiac arrest after an alcohol intoxication with a return of spontaneous circulation after 230min of mechanical cardiopulmonary resuscitation and rewarming by veno-arterial ECMO with femoral cannulation and retrograde perfusion of the aortic arch. Despite functional veno-arterial ECMO, we continued mechanical cardiopulmonary resuscitation (Auto Pulse™ device, ZOLL Medical Corporation, Chelmsford, USA) until return of spontaneous circulation to prevent left ventricular distention from persistent ventricular fibrillation. The case was further complicated by extensive trauma caused by mechanical cardiopulmonary resuscitation (multiple rib fractures, significant hemothorax, and a liver laceration requiring massive transfusion), lung failure necessitating a secondary switch to veno-venous ECMO, and acute kidney injury with the need for renal replacement therapy. Shortly after return of spontaneous circulation, the patient was already following commands and could be discharged 3 weeks later without neurologic, cardiac, or renal sequelae and being entirely well. Prolonged accidental hypothermic cardiac arrest might present with excellent outcomes when supported with veno-arterial ECMO. Until return of spontaneous circulation, one might consider continuing with mechanical cardiopulmonary resuscitation in addition to ECMO to allow some left ventricular unloading. However, the clinician should keep in mind that prolonged mechanical cardiopulmonary resuscitation may cause severe injuries.